A representação judaica na poesia mariana ibérica no século XIII: análise das cantigas de Santa Maria de Afonso X, o sábio - Pereira, Ingrid Alves (2019)
It investigates the gradual stigmatization of Jews through historiographic, literary and discursive bias, analyzing the miracles contained in Alfonso X's Cantigas de Santa Maria of the 13th century, which often deal with Jews with a derogatory tone, placing them in a marginal position in relation to Christians. It discusses the representation of this religious minority through an interdisciplinary approach that encompasses Cultural History, by Roger Chartier (1990); from discourse analysis by Patrick Charaudeau and Dominique Maingueneau (2004) and from philological-literary studies by Walter Mettman (1989). It notes that during the Middle Ages, the Iberian context differs profoundly from the rest of Europe, as the Christian "Reconquest" of Muslim dominated territories shaped a different situation from other places, benefiting Jews. In this context, the relationship between the three religions (Christian, Jewish and Muslim) was of relative mutual tolerance; However, there is a growing hostility to the Jewish minority represented in the Christian literature from the 13th century, which can be seen in the Marian songs of Alfonso X.